Monetary‐Fiscal Interactions and the Problem of Outdated Commitments: Eurozone Crisis Versus Covid‐19 - Sebastian Diessner; Philipp Genschel (Politics and Governance)
Post-crisis accounts of economic governance in Europe have often analysed the monetary policy decisions of the supranational European Central Bank and the fiscal policy coordination of the intergovernmental Council and Eurogroup separately. This is unfortunate since both policy fields are closely linked and increasingly interdependent. We put forward a theory of monetary-fiscal interactions in the Economic and Monetary Union based on the notion of de-commitment and re-commitment. In juxtaposition to the grand theories of neo-functionalism and liberal intergovernmentalism, we argue that EU institutions serve not only to tie the member states to policy commitments but also to untie them from previous policy commitments that have become outdated and harmful. The European Central Bank’s main contribution to safeguarding the Eurozone in 2012 and 2020 has not been to enforce but to relax the monetary financing prohibition of the Treaty, and the Council’s main contribution in 2020 was not to double down on the no bail-out clause but to re-commit to risk-sharing and burden-sharing through the NextGenerationEU programme. We argue and show that economic governance in Europe has progressed through three stages of commitment. Whereas monetary-fiscal interactions followed a commitment logic during the first decade of the Economic and Monetary Union (the “old normal”), the defining feature of the second decade has been de-commitment (the “new normal”). In the Covid-19 crisis, economic governance finally entered a phase of re-commitment (taking the Economic and Monetary Union “back to the future”). The analysis has implications for our understanding of the purpose and power of supranational institutions in overcoming the problem of outdated commitments post-crisis.